La empresa multinacional y la decisión de exportar o adaptar sus prácticas de dirección de recursos humanos - Aitziber Lertxundi Lertxundi (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
This study analyses the readiness of multinational enterprises to export their human resource management (HRM) system to their subsidiaries abroad, depending on the perceived quality of the system and the differences in the cultural contexts of the headquarters and subsidiaries. Using a qualitative exploratory study and another quantitative study of a sample of 58 Spanish industrial multinationals and their affiliates, we conclude that the quality of the headquarters-based HRM system has a significant influence when it comes to deciding whether to export it to the subsidiary, whereas the difference in cultural contexts is not decisive when transferring the basic principles of the human resources system, although it possibly is decisive in the transfer of practices and sub-processes.
Keywords: F23; M12; 330; transfer of HRM practices; best practices; high performance work systems; national culture; Spain